Media Literacy and the Effect of Socialization - Trültzsch-Wijnen, Christine W. (Springer eBook Collection, 2020)
Chapter 1. Introduction: On the Multiple Facets of Media Literacy -- Part I: Social and Individual Aspects of Media Activity -- Chapter 2.The Significance of Media For Processes of Socialization -- Chapter 3.‘Distinctions’ in Media Activity -- Part II: Competence, Performance and Media Literacy -- Chapter 4.Theoretical Approach to the Concepts of Competence and Performance -- Chapter 5. Competence and Literacy in Relation to Media -- Part III: Empirical Perspectives -- Chapter 6. Researching Media Literacy and the Appropriation of Media -- Chapter 7. Media Competence and Media Performance in Using the Social Web -- Chapter 8. Conclusion: Sensitivity and Open-Mindedness are Needed -- Chapter 9. Appendix.
https://katalog.adlr.link/Record/0-1741571359